2018
DOI: 10.1021/jacs.8b11840
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbonyl-Olefin Metathesis of Aliphatic Ketones: Iron(III) Homo-Dimers as Lewis Acidic Superelectrophiles

Abstract: Catalytic carbonyl-olefin metathesis reactions have recently been developed as a powerful tool for carbon-carbon bond formation. However, currently available synthetic protocols rely exclusively on aryl ketone substrates while the corresponding aliphatic analogs remain elusive. We herein report the development of Lewis acid-catalyzed carbonyl-olefin ring-closing metathesis reactions for aliphatic ketones. Mechanistic investigations are consistent with a distinct mode of activation relying on the in situ format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 63 publications
0
60
0
Order By: Relevance
“…We have recently shown that Lewis acidic superelectrophiles can function as potent catalysts for the activation of less reactive substrates in carbonyl-olefin metathesis reactions. [15] Specifically, suitable silver salts can abstract halides X from neutral metal complexes MX n resulting in the formation of superelectrophilic heterobimetallic ion pairs. [16] Based on these results, we next evaluated various Lewis acid superelectrophiles, obtained via chloride abstraction from neutral Lewis acids, for their ability to catalyze the formation of 8.…”
mentioning
confidence: 99%
“…We have recently shown that Lewis acidic superelectrophiles can function as potent catalysts for the activation of less reactive substrates in carbonyl-olefin metathesis reactions. [15] Specifically, suitable silver salts can abstract halides X from neutral metal complexes MX n resulting in the formation of superelectrophilic heterobimetallic ion pairs. [16] Based on these results, we next evaluated various Lewis acid superelectrophiles, obtained via chloride abstraction from neutral Lewis acids, for their ability to catalyze the formation of 8.…”
mentioning
confidence: 99%
“…8,9 In contrast with the diene RCM, it is achieved from readily available ene-arylketones, or more recently using aliphatic ketones, 10 using simple Lewis acids. Iron(III) complexes have been especially utilized for that purpose, mostly by Schindler et al 9,10 Due to our interest in the development of galliumcatalyzed transformations, 11 and our recent work on the gallium-catalyzed transfer hydrogenation of alkenes using 1,4-cyclohexadiene as hydrogen donor, 12,13 we decided to investigate a tandem process combining a carbonyl-olefin metathesis and a transfer hydrogenation to form cycloalkanes (Scheme 1B). We kept in mind that the judicious installation of substituents (R 1 and R 2 ) could allow the formation of two contiguous stereocenters and possibly address the issue of the formation of 1,2-cis-disubtituted cyclopentanes.…”
mentioning
confidence: 99%
“…Using a catalytic amount of an equimolar mixture of GaCl3/GaBr3 (entry 6) increased proportion of 3a, suggesting the formation of a heterobimetallic superelectrophile known to have a higher Lewis acidity than the homobimetallic (GaCl3)2 superelectrophilic dimer. 10 The intervention of superelectrophilic species in this chemistry will be further discussed below and in the Supporting Information (IR and DFT studies). When using a catalytic mixture of GaCl3 and AgSbF6, the desired product 3a was observed as major component of the mixture but significant decomposition lowered the isolated yield to 27% (entry 7).…”
mentioning
confidence: 99%
See 2 more Smart Citations